Distribution of the number of spanning regular subgraphs in random graphs1. Issue 3 (4th April 2012) - Gao, Pu
Abstract In this paper, we examine the moments of the number of d ‐factors in <![CDATA[articlemathrsfs, amsmath, amssymbemptydocumentalign* G(n, p)align* document]]> <inline-graphic xlink:href="ark:/27927/pgg2pr8ckgs" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> for all p and d satisfying d3 = o(p2n). We also determine the limiting distribution of the number of d ‐factors inside this range with further restriction that <![CDATA[articlemathrsfs, amsmath, amssymbemptydocumentalign*(1-p)dn→∞align* document]]> <inline-graphic xlink:href="ark:/27927/pgg2pr8ckhb" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> as n →∞.© 2012 Wiley Periodicals, Inc. Random Struct. Alg., 2013